Synchrotron-based Transmission X-ray Microscopy (TXM) Observations of Fully Hydrated Blood Platelets and Their Activation Process - Yang, Nuri; Nho, Hyun Woo; Kalegowda, Yogesh; Kim, Jin Bae; Song, Jaewoo; Shin, Hyun-Joon; Yoon, Tae Hyun (Bulletin of the Korean Chemical Society, 2014)
Platelets are anuclear discoid-shaped blood cells with key roles in human body. To understand the mechanisms of their activation process, it is required to have analytical imaging techniques capable of acquiring platelet images under fully hydrated conditions. Herein, for the first time, we demonstrate the capability of synchrotronbased transmission X-ray microscopy (TXM) to study platelets (resting and ADP activated) under hydrated and air-dried conditions. To confirm the biological imaging capability of TXM, fixed platelets were imaged and compared with whole mount electron microscopy (EM) images. TXM provided morphological information with sufficient spatial resolution with simple and quick sample preparation procedure. We also observed temporal changes during the platelet activation, which initially had a discoid shape (0 s), formed pseudopodia (30 s) and generated a network of fibrin (5 min). Our results clearly demonstrate the potential of TXM technique to study fully hydrated biological samples under in situ conditions. KCI Citation Count: 4